Effectiveness of the capability approach in rehabilitation for persons with neuromuscular diseases: A controlled before-after study - Eirlys J. Pijpers; Bart Bloemen; Wija J. Oortwijn; Baziel G. M. van Engelen; Gert Jan van der Wilt; Jan T. Groothuis; Edith H. C. Cup (PLoS ONE, 2025)
Background Rehabilitation of persons with neuromuscular diseases (NMD) requires a personalised approach that focuses on achieving and maintaining a level of functioning that enables them to be in a state of well-being. The capability approach states that well-being should be understood in terms of capabilities, which are the opportunities that people have to be and do things they have reason to value. The aim of this study is to investigate whether providing care inspired by the capability approach (capability care) has an effect on the well-being of persons with NMD. Methods In the Rehabilitation and Capability care for persons with NeuroMuscular Diseases (ReCap-NMD) study, 64 adults with facioscapulohumeral muscular dystrophy or myotonic dystrophy type 1 were included in two groups, using a before-after controlled design with 6 months between the measurement moments. The first group received rehabilitation as usual, the second received capability care. This article reports on the primary outcome measure, the Canadian Occupational Performance Measure (COPM) and secondary quantitative outcome measures (questionnaires on participation, capability well-being and health-related quality of life). Results There was no difference between capability care and usual care on the COPM and the secondary outcome measures. There was a similar improvement for both capability care and usual rehabilitation on the COPM at 6-month follow-up. This means that the effect of capability care is similar to usual rehabilitation. Conclusion This is the first study that explicitly developed, implemented and evaluated a clinical healthcare intervention inspired by the capability approach. We found no difference on the COPM between persons with NMD receiving capability care compared to usual rehabilitation. There is a need for further research on the clinical relevance and added value of the capability approach for rehabilitation and other fields in healthcare. Trial registration Trialregister.nl NL8946.